2015
DOI: 10.1111/jcmm.12585
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac regenerative potential of cardiosphere‐derived cells from adult dog hearts

Abstract: The regenerative potential of cardiosphere-derived cells (CDCs) for ischaemic heart disease has been demonstrated in mice, rats, pigs and a recently completed clinical trial. The regenerative potential of CDCs from dog hearts has yet to be tested. Here, we show that canine CDCs can be produced from adult dog hearts. These cells display similar phenotypes in comparison to previously studied CDCs derived from rodents and human beings. Canine CDCs can differentiate into cardiomyocytes, smooth muscle cells and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 29 publications
2
24
1
1
Order By: Relevance
“…Derivation and culture of cCDCs Canine CDCs were generated and expanded as described [3,12] from myocardial specimens of a healthy male beagle dog [8,13]. Briefly, this tissue was surgically collected from the right ventricle of a 2-year-old canine beagle.…”
Section: Methodsmentioning
confidence: 99%
“…Derivation and culture of cCDCs Canine CDCs were generated and expanded as described [3,12] from myocardial specimens of a healthy male beagle dog [8,13]. Briefly, this tissue was surgically collected from the right ventricle of a 2-year-old canine beagle.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiospheres (CSps) are cardiac‐derived multicellular clusters, considered a reliable in vitro model of the cardiac microenvironment, hosting a reservoir of both immature and committed progenitors towards the three major cardiac cell lineages: cardiomyocytes, endothelial cells (ECs) and smooth muscle cells (SMCs) . CSps transplantation into infarcted hearts results in enhanced in vivo cell survival and cardioprotection . Recent data have shown that activation of the Notch signalling pathway promotes cell differentiation along the vascular smooth muscle lineage in CSp‐derived cells and is sensitive to oxygen tension in the tridimensional cellular array …”
Section: Introductionmentioning
confidence: 99%
“…21 CSps transplantation into infarcted hearts results in enhanced in vivo cell survival and cardioprotection. 22 Recent data have shown that activation of the Notch signalling pathway promotes cell differentiation along the vascular smooth muscle lineage in CSp-derived cells and is sensitive to oxygen tension in the tridimensional cellular array. 23 In this work, we aimed at dissecting the specific role of Notch1 signalling in CSps.…”
mentioning
confidence: 99%
“…In animal experiments, cardiac stem cells were injected into the heart of mice with heart disease, and the injected cells directly migrated to the damaged heart tissue, promoted the regeneration of myocardium, and improved the ability of the heart to pump blood [44] . Multiple types of CSCs have been identified including Islet-1+ cells, Sca-1+ cells, cardiosphere derived cells (CDCs), cardiac mesoangioblasts, cardiac specific side population, and epicardial progenitors [45][46][47][48][49][50] . A lot of preclinical researches in both small and large animal models have indicated the potential of CSCs therapy in treating MI (Table1).…”
Section: Cardiac Stem Cellsmentioning
confidence: 99%